Cywilnoprawne aspekty umów zawieranych pomiędzy organem administracji publicznej a organizacją pozarządową w celu realizacji zadań publicznych - Biniasz-Celka, Danuta (Studia Prawa Publicznego, 2019)
The article focuses on selected aspects of collaboration between public authorities and public benefit organizations (PBOs). PBOs not only enable the development of active citizenship, but also contribute to the effective implementation of public tasks, thus helping the authorities in implementing their statutory duties. An outcome of the collaboration may be, among other things, an agreement to implement certain tasks, taking the form of, for example, the realization of a task or the support provided for its realization following competitive tendering and in justified cases without the tender, or performed within the framework of a local initiative. The main focus of the article is to determine the scope of the autonomy of the parties in the classic approach, keeping in mind that the autonomy is one of the main principles governing civil law. Parties in a civil law contract must be able to create autonomous relationships. Consequently, in order to fulfil its functions, civil law must be an open system which regulates typical situations in a non-authoritative manner. The essential question seems to be to what extent this attitude may be transposed to public law. Undoubtedly, an agreement as a form of an administrative activity will never have the same legal nature as an agreement concluded between private parties. An administrative body that applies private law forms of action does not become subject to the same rights as a private entity and, consequently, is not exempt from the obligation to comply with the fundamental constitutional principles and values that have been established with a view of protecting civil rights and freedoms.